2016
DOI: 10.4143/crt.2014.351
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Blood Lymphocyte Count during Preoperative Chemoradiotherapy as a Predictive Marker for Pathologic Complete Response in Locally Advanced Rectal Cancer

Abstract: PurposeThe objective of this study was to explore the relationship between the circulating lymphocyte level during preoperative chemoradiotherapy (CRT) and pathologic complete response (pCR) in locally advanced rectal cancer.Materials and MethodsFrom May 2010 to May 2013, 52 patients treated with preoperative CRT followed by surgery, were analysed. Patients received conventional fractionated radiotherapy (50-54 Gy) with fluorouracil-based chemotherapy. Surgical resection was performed at 4 to 8 weeks after the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 21 publications
4
30
2
Order By: Relevance
“…In our study we found that a high pre-CRT total lymphocytes count in the peripheral blood of rectal cancer patients was significantly associated with pathological response and high regression rate, and this as reported by Kitayama et al, Choi [24] who failed to find significant correlation between baseline blood lymphocyte counts with pCR and he explained this because they excluded patients with baseline lymphopenia from their study populations before preoperative CRT. Lymphopenia initially and lymphopenia as treatment effect has a negative prognostic value in various settings and malignancies [25] It was previously demonstrated that the densities of CD4(+) and CD8(+) tumor-infiltrating lymphocytes (TIL) had significant association with the histological grade after CRT, also in achieving CR post CRT and the density of CD8(+)…”
Section: Discussionsupporting
confidence: 81%
“…In our study we found that a high pre-CRT total lymphocytes count in the peripheral blood of rectal cancer patients was significantly associated with pathological response and high regression rate, and this as reported by Kitayama et al, Choi [24] who failed to find significant correlation between baseline blood lymphocyte counts with pCR and he explained this because they excluded patients with baseline lymphopenia from their study populations before preoperative CRT. Lymphopenia initially and lymphopenia as treatment effect has a negative prognostic value in various settings and malignancies [25] It was previously demonstrated that the densities of CD4(+) and CD8(+) tumor-infiltrating lymphocytes (TIL) had significant association with the histological grade after CRT, also in achieving CR post CRT and the density of CD8(+)…”
Section: Discussionsupporting
confidence: 81%
“…Despite the small number of patients (n=10) with a min ALC<297 cells/μL, min ALC was significantly related to poor survival in multivariate analysis (P=0.038). Two small studies on lymphopenia and tumor response during RT seem to support this data, but few studies have examined survival prediction by lymphopenia during RT [8,22]. Post ALC was the strongest predictor of OS and PFS in LS-SCLC (P=0.016 and P=0.01, respectively).…”
Section: Discussionmentioning
confidence: 76%
“…Circulating lymphocyte count in peripheral blood was found to be an important parameter to determine clinical outcomes in advanced rectal cancer [5]. We also recently confirmed that sustaining lymphocyte count during preoperative CRT could be a predictive factor in rectal cancer [6]. …”
Section: Introductionmentioning
confidence: 79%
“…Each subpopulation of lymphocytes has different immune functions and different responses to CRT [14]. In a previous study, we showed that change in lymphocytes during CRT was associated with a pCR in locally advanced rectal cancer [6]. This result inspired us to evaluate the relationship between subpopulations of lymphocytes and tumor response.…”
Section: Discussionmentioning
confidence: 99%